AI 2009: Advances in Artificial Intelligence 22nd Australasian Joint Conference, Melbourne, Australia, December 1-4, 2009, Proceedings - Nicholson, Ann; Li, Xiaodong (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the refereed proceedings of the 22nd Australasian Joint Conference on Artificial Intelligence, AI 2009, held in Melbourne, Australia, in December 2009. The 68 revised full papers presented were carefully reviewed and selected from 174 submissions. The papers are organized in topical sections on agents; AI applications; computer vision and image processing; data mining and statistical learning; evolutionary computing; game playing; knowledge representation and reasoning; natural language and speech processing; soft computing; and user modelling.